2015
DOI: 10.1152/ajprenal.00417.2014
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine reverses maternal cigarette smoke exposure-induced renal oxidative stress and mitochondrial dysfunction in mouse offspring

Abstract: Maternal smoking is associated with metabolic disorders, renal underdevelopment, and a predisposition to chronic kidney disease in offspring, yet the underlying mechanisms are unclear. By exposing female Balb/c mice to cigarette smoke for 6 wk premating and during gestation and lactation, we showed that maternal smoke exposure induced glucose intolerance, renal underdevelopment, inflammation, and albuminuria in male offspring. This was associated with increased renal oxidative stress and mitochondrial dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 27 publications
12
69
1
Order By: Relevance
“…Our results may suggest that LC‐mediated reduction of FGF2 at weaning may potentially prevent fibrogenesis in the long term. Indeed, in our previous study, the renal expression of the inflammatory marker MCP‐1 in adulthood was significantly reduced in SE offspring if the mothers had LC supplementation during gestation and lactation compared to those from the SE mothers without intervention . The long‐term anti‐inflammatory effect of maternal LC supplementation in the kidneys of the adult offspring is consistent with a previous study …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results may suggest that LC‐mediated reduction of FGF2 at weaning may potentially prevent fibrogenesis in the long term. Indeed, in our previous study, the renal expression of the inflammatory marker MCP‐1 in adulthood was significantly reduced in SE offspring if the mothers had LC supplementation during gestation and lactation compared to those from the SE mothers without intervention . The long‐term anti‐inflammatory effect of maternal LC supplementation in the kidneys of the adult offspring is consistent with a previous study …”
Section: Discussionsupporting
confidence: 90%
“…In rodents, LC supplementation has been shown to improve atherosclerosis and chronic renal failure induced by partial nephrectomy . In addition, LC has been shown to be essential in fetal development and intrauterine maturation of the brain and lung; we have recently demonstrated that maternal LC supplementation during gestation and lactation reversed small body weight and kidney weight at birth, as well as normalising renal oxidative stress and renal dysfunction due to maternal SE in the male offspring . However, the effect of LC on epigenetic signatures and renal developmental markers is not known.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Together, these SOD enzymes scavenge superoxide anion into molecular oxygen and hydrogen peroxide, then CAT and GPx reduce hydrogen peroxide, thus preventing production of highly toxic hydroxyl radical [64]. Growing evidence indicates that cigarette smoking or CSE significantly decrease the activities of anti-oxidative enzymes both in vitro and in vivo researches [65,66]. In the present study, our results displayed a significant reduction in activities of SOD1, SOD2, CAT and total GPx in CSE rat placentas, however, the decreased activities of the anti-oxidative enzymes were improved with NaHS application.…”
Section: Discussionmentioning
confidence: 99%
“…However, L-carnitine has been shown to improve symptoms in children with moderate persistent asthma when administered orally 43 . Dietary supplementation of L-carnitine has also been shown to reverse renal oxidative stress and mitochondrial dysfunction in female BALB/c mice who were exposed to cigarette smoke 44 . In a recent study, L-carnitine decreased with emphysema progression in mice, and L-carnitine supplementation improved lung function and reduced apoptosis 13 .…”
Section: Discussionmentioning
confidence: 99%